2002
DOI: 10.1091/mbc.01-10-0472
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between Paralogs using Microarray Analysis: Application to the Yap1p and Yap2p Transcriptional Networks

Abstract: Ohno [Ohno, S. (1970) in Evolution by Gene Duplication, Springer, New York] proposed that gene duplication with subsequent divergence of paralogs could be a major force in the evolution of new gene functions. In practice the functional differences between closely related homologues produced by duplications can be subtle and difficult to separate experimentally. Here we show that DNA microarrays can distinguish the functions of two closely related homologues from the yeast Saccharomyces cerevisiae, Yap1p and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 25 publications
4
56
0
Order By: Relevance
“…(As a baseline comparison, the average overlap between the Yaps and an unrelated TF, Pdr1, was 2.9% under nominal conditions.) This result confirmed and expanded previous observations that Yaps have partially overlapping but nonredundant functions (5,6,19).…”
Section: Genome-wide Promoter Binding Profiles Of Yapssupporting
confidence: 92%
See 2 more Smart Citations
“…(As a baseline comparison, the average overlap between the Yaps and an unrelated TF, Pdr1, was 2.9% under nominal conditions.) This result confirmed and expanded previous observations that Yaps have partially overlapping but nonredundant functions (5,6,19).…”
Section: Genome-wide Promoter Binding Profiles Of Yapssupporting
confidence: 92%
“…Studies suggest that Yaps 2 and 6 can function either as activators or repressors, depending on the regulated genes (6,29,30). To further explore this phenomenon and its underlying mechanisms, we applied network component analysis (NCA) (31) to infer the regulatory directions (activating, repressing) of each Yap on its target genes.…”
Section: Yaps 2 4 5 and 6 But Not Yap1 Can Function As Both Activamentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of global gene expression using microarrays has shown that although Yap1p and Yap2p are both involved in the response to cellular stresses, they regulate different regulons (7). The mechanism(s) of Yap1p/Yap2p gene selectivity are not understood but may include variations in the base pairs flanking the consensus Yap binding site (7).…”
mentioning
confidence: 99%
“…Other putative targets of Yap2 that encode activities involved in protein folding have been suggested by microarray analyses, but these have not yet been validated [37]. It has also Cd C356 C391 Yap2 Fig.…”
Section: Discussionmentioning
confidence: 99%